2009
DOI: 10.1073/pnas.0905212106
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic cytosolic and mitochondrial phenylalanyl-tRNA synthetases catalyze the charging of tRNA with the meta -tyrosine

Abstract: The accumulation of proteins damaged by reactive oxygen species (ROS), conventionally regarded as having pathological potentials, is associated with age-related diseases such as Alzheimer's, atherosclerosis, and cataractogenesis. Exposure of the aromatic amino acid phenylalanine to ROS-generating systems produces multiple isomers of tyrosine: m-tyrosine (m-Tyr), o-tyrosine (o-Tyr), and the standard p-tyrosine (Tyr). Previously it was demonstrated that exogenously supplied, oxidized amino acids could be incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 32 publications
3
79
0
Order By: Relevance
“…These tRNA aminoacylation levels are comparable to those previously reported in other bacterial systems using similar methods, as is the observed increase in deacylated tRNA upon starvation (20)(21)(22). When the strains were grown under amino acid stress conditions in the presence of physiologically relevant levels of the natural noncognate PheRS substrate m-Tyr (3,23,24), levels of aa-tRNA Phe were 23% higher in the editing-deficient strain than in the wild type. These results also revealed that the cellular ratio of aminoacylated to deacylated tRNA increases significantly in the absence of PheRS editing, particularly under amino acid stress conditions ( Fig.…”
Section: Ablation Of Phers Editing Alters the Cellular Ratio Of Aminosupporting
confidence: 72%
“…These tRNA aminoacylation levels are comparable to those previously reported in other bacterial systems using similar methods, as is the observed increase in deacylated tRNA upon starvation (20)(21)(22). When the strains were grown under amino acid stress conditions in the presence of physiologically relevant levels of the natural noncognate PheRS substrate m-Tyr (3,23,24), levels of aa-tRNA Phe were 23% higher in the editing-deficient strain than in the wild type. These results also revealed that the cellular ratio of aminoacylated to deacylated tRNA increases significantly in the absence of PheRS editing, particularly under amino acid stress conditions ( Fig.…”
Section: Ablation Of Phers Editing Alters the Cellular Ratio Of Aminosupporting
confidence: 72%
“…Modifi ed amino acids could originate from protein-bound amino acids [ 11 ] or may be incorporated into proteins during their synthesis resulting in a polypeptide without direct oxidative damage of the protein itself [ 15 -17 ] . In line with these fi ndings, free m -Tyr was shown to be incorporated into cellular proteins, possibly via protein synthesis, which then can exert cytotoxic actions [ 17 ] . Furthermore, o -Tyr and m -Tyr levels were found to be signifi cantly higher in the aortic tissue of hyperglycemic cynomolgus monkeys and that of rats with aortic banding-induced hypertension [ 11 , 18 ] .…”
Section: Elevated Vascular Level Of Ortho -Tyrosine Contributes To Thmentioning
confidence: 54%
“…The water molecule W23 generates an extensive HB network with the amide group of Valβ324 (2.8 Å) and the main chain carbonyl oxygen of Alaβ262 (17,23,24). The aromatic rings of the ligands are rotated relative to each other, and slightly shifted (Fig.…”
Section: Resultsmentioning
confidence: 99%